Disciplining creativity: tensions between discourses of 'creative environments' and discourses of surveillance/normalisation in a school institution. Issue 6 (1st November 2020) - Gormley, Kevin
ABSTRACT: To understand patterns of co-option and tension between discourses of creativity on the one hand, and discourses of school management and administration on the other, it is important to bring these discourses into contact with each other. This paper considers ideas of risk-taking, autonomy, novelty and flexibility, all of which are frequently cited in describing environments conducive to creativity in schools, alongside the experiences of four teachers working in a particular school site. It engages with interview data, as well as Foucault's writings on disciplinary power, to argue that some priorities of school administration, such as the steering effects of comparative assessments and parents' expectations, are difficult to align with ideas of autonomy and risk in school settings. The analysis presented here offers a situated account of discourses of creative environments in the context of wider power relations that traverse the school.